Comprehensive Evaluation of Salt Tolerance in Asparagus Germplasm Accessions (Asparagus officinalis L.) at Different Growth Stages - Huimin Gao; Xuhong Zhang; Yuqin Liang; Lingdi Dong; Changzhi Han; Yanpo Cao (Journal of Food Quality)
The screening and cultivation of salt-tolerant crops are becoming more and more important owing to the constant increase in the saline soil area worldwide. Asparagus (A. officinalis L.) is a highly nutritious vegetable crop and widely consumed globally for a long time; however, little research has been done on asparagus. In this study, the salt tolerance of 95 asparagus germplasm accessions was evaluated at three growth stages (germination, seedling, and adult stages) under both salt-stressed and control conditions. Results showed that the growth parameters of most germplasm accessions were obviously inhibited by salt stress. The mean value of the seed germination rate at the germination stage decreased by half under salt-stressed conditions, the mean salt-injury index at the seedling stage reached 57.68%, and the fresh weight of the aboveground part (FWA) and the dry weight of the aboveground part (DWA) decreased the most among the traits determined at the adult stage by more than 60%. Our study screened out 30, 19, and 18 tolerant germplasm accessions (including highly salt-tolerant and salt-tolerant germplasm accessions) at the germination stage, seedling stage, and adult stage, respectively. Among them, two germplasm accessions (Ji08-2 and Jx1502) were simultaneously identified to be tolerant in all three growth stages, while other germplasm accessions were tolerant only at one or two stages. Thus, the salt tolerance of asparagus has periodic characteristics and changes throughout the lifecycle, and the identification of salt tolerance at all the main growth stages facilitates adequate assessment and application of tolerant germplasm accessions.